AB0670 Ankylosing Spondylitis (AS-P) Patient Centred Education Program Improves Disease Activity and Quality of Life up To 12 Months. (15th July 2016) - Inderjeeth, C.A.; Raymond, W.; Connor, C.; Edelman, J.; Cook, N.; Briffa, K.; McQuade, J.
Abstract : Background: Patient centered education interventions are rare. After a needs assessment, focus group consultation, and execution of a Plan, Do, Study, Act (PDSA) model, we developed and delivered a multidimensional Ankylosing Spondylitis Education Program (AS-P) to patients referred via a rheumatologist (meeting the New York criteria for AS). Objectives: To examine the benefits of AS-P for people with Ankylosing Spondylitis (AS) in regards to health status, quality of life and disease activity. Methods: 79 people were recruited in the intervention. Exclusion criteria: <18yo; non-English speaking; comorbid inflammatory musculoskeletal disease; and/or visual, auditory, or cognitive impairment. Participants attended a weekly 2.5 hour patient centered education session facilitated by same two health professionals over 6 weeks. The scripted content included multidimensional strategies including stretches; self-efficacy and self-management constructs and optional 7th week supervised exercise class. Data collection included demographic, AS disease management characteristics, medication patterns, and outcomes, measured at baseline, 6 weeks, 3 months, 6 months and 12 months using GLM repeated measures ANOVA. Additional outcomes included the: BAS-G, BASDAI, AS-Qol, BASFI, back pain (VAS), PDGA, anxiety (HADs), health distress (HDQ), quality of life (EASIQol), perceived health (GPH), pain (PSEQ), MAFs and SF-36. Results: At baseline, 43.3% were male and the mean age was 43.5 ±14.5 years. The median time to AS diagnosis from the index symptom experience was 4 years IQR (1–11). The only significant change in medication usage occurred between Month 3 to Month 6 (p=0.018). The BAS-G, BASDAI and the AS-QoL had improved between baseline to 3, 6 and 12 months (all p<0.05). Nocturnal and total back pain had improved between baseline and 12 months (all p<0.05). The PDGA and HDQ had improved between baseline and 12 months (all p<0.05). The EASI-QOL (physical health composite) had improved at 3 and 12 months (p<0.05). There was also a positive trend in the EASIQOL disease activity, emotional state and social composite scores (p>0.05). MAFs demonstrated a sustained improvement over 12 months (p=0.011). Similarly, the SF-36 physical (p=0.001) and mental (p=0.002) composite scores had improved 12 months post-intervention. BASFI (p=0.271) and HADs (p=0.086) demonstrated no improvement 12 months post-intervention. Conclusions: AS-P for AS is effective in improving AS specific disease activity, pain and QOL scores for up to 12 months. References: Von Korff, M et al (2002) Organising care for chronic illness. BMJ 325: 92–94. Zochling, J (2011) Measures of symptoms and disease status in ankylosing spondylitis. Arthritis Care & Research 63: S47-S58. Disclosure of Interest: None declared